2010
DOI: 10.1002/humu.21274
|View full text |Cite
|
Sign up to set email alerts
|

First missense mutation in the SOST gene causing sclerosteosis by loss of sclerostin function

Abstract: Sclerosteosis is a rare bone dysplasia characterized by greatly increased bone mass, especially of the long bones and the skull. Patients are tall, show facial asymmetry and often have syndactyly. Clinical complications are due to entrapment of cranial nerves. The disease is thought to be due to loss-of-function mutations in the SOST gene. The SOST gene product, sclerostin, is secreted by osteocytes and transported to the bone surface where it inhibits osteoblastic bone formation by antagonizing Wnt signaling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…SOST is involved in bone homeostasis, in particular and acts as a direct extracellular antagonist of canonical Wnt signaling by binding to lipoprotein receptor-related protein-5/6 (LRP5/6) (Krause et al 2010;Semënov et al 2005). Loss of function of SOST causes high bone mineral density in humans (Piters et al 2010;Bhadada et al 2013), while SOST overexpression in transgenic mice leads to reduced bone formation and osteopenia (Winkler et al 2003). SOST can regulate mechanical and inflammatory bone remodeling (Robling et al 2008;Heiland et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…SOST is involved in bone homeostasis, in particular and acts as a direct extracellular antagonist of canonical Wnt signaling by binding to lipoprotein receptor-related protein-5/6 (LRP5/6) (Krause et al 2010;Semënov et al 2005). Loss of function of SOST causes high bone mineral density in humans (Piters et al 2010;Bhadada et al 2013), while SOST overexpression in transgenic mice leads to reduced bone formation and osteopenia (Winkler et al 2003). SOST can regulate mechanical and inflammatory bone remodeling (Robling et al 2008;Heiland et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…19 Mutations in SOST gene causing sclerostin loss of function are associated with a clinical syndrome of progressive bone thickening known as sclerosteosis. 20,21 Efficacy of a monoclonal sclerostin neutralizing antibody (Scl-Ab) to increase bone mass and strength and in promoting fracture healing has been demonstrated in several animal models including female osteoporotic rats, aged male rats, and gonad-intact non-human primates. …”
mentioning
confidence: 99%
“…19 Mutations in SOST gene causing sclerostin loss of function are associated with a clinical syndrome of progressive bone thickening known as sclerosteosis. 20,21 Efficacy of a monoclonal sclerostin neutralizing antibody (Scl-Ab) to increase bone mass and strength and in promoting fracture healing has been demonstrated in several animal models including female osteoporotic rats, aged male rats, and gonad-intact non-human primates. 5,6,22 We previously used a critical sized 6 mm defect in the Lewis rat femur to evaluate the effects of Scl-Ab treatment on critical sized bone defect healing and found that it led to increased bone formation, but complete healing of the femoral defects occurred in only a small subset of rats.…”
mentioning
confidence: 99%
“…Recent advances in molecular genetics have revealed that both of them are caused by functional mutations in the SOST gene, which is localized in the 17q12-21 chromosomal region and codes for sclerostin, a glycoprotein that is solely expressed by osteocytes. [3][4][5][6] Sclerostin acts as a negative regulator of bone formation, through inhibition of the Wnt signaling pathway, which is of critical importance for the development and function of osteoblasts. 7 Undetectable or very low levels of sclerostin in these patients result in excessive bone growth and increased bone strength 8 ( Figure 1).…”
Section: Meostasismentioning
confidence: 99%
“…9 It is caused by 6 different types of lossof-function mutations of the SOST gene, resulting in reduced production of sclerostin, and is inherited in an autosomal-recessive mode. 6 All patients are homozygous for these mutations and the complete absence of sclerostin results in overgrowth of skull bones, mandible, ribs, clavicles, long bones and pelvis. Patients are usually tall and have a characteristic face because of the facial deformities of bossing of the forehead and enlargement of the mandible.…”
Section: Sclerosteosismentioning
confidence: 99%